Prevalence and clinical characteristics of pediatric cystinuria in Ahvaz, southwest of Iran: Pediatric cystinuria in Ahvaz - Fathi , Mohsen; Valavi , Ehsan; Pourchitsaz, Marziyeh; Amuri , Parisa; Fathi , Mohammad Reza (Jordan Medical Journal, 2024)
Objective: This retrospective hospital-based study is aimed at investigating the 6-year prevalence and clinical characteristics of pediatric cystinuria in Ahvaz, southwest of Iran. Method: Demographic and clinical data belonging to children with kidney stone disease (KSD) who referred to nephrology wards were obtained from the medical records. Then, data were statistically analyzed and compared between the two groups of children with non-cystine kidney stones and those with cystinuria. Results: From a total of 415 patients with KSD, 45 cases (10.8%) had cystinuria and 370 cases (89.2%) had non-cystine kidney stones. Overall, the incidence rate of KSD was higher in boys (53.7%) than girls (46.3%, p=0.03). However, no significant difference in age and gender was observed between the two groups (p>0.05). Parental consanguinity [OR (95%):4.1(2.15_7.8), p=0.0001] and bilateral renal involvement [OR (95%):2.38(1.25_4.53), p=0.01] were more frequent among children with cystinuria. The number and size of cystine stones were significantly higher than non-cystine stones [p=0.0001]. Hypercalciuria (60.72%) and hyperuricosuria (40.1%) were the most frequent metabolic disorders, which were significantly more frequent in patients with non-cystine stones (p<0.01). The rate of complete recovery in cystinuria patients was significantly lower than in patients with non-cystine stones (51% vs 83.2%, p=0.0001). Conclusion: Parental consanguinity may increase the risk of cystinuria development. Also, notable prevalence of symptomatic cystinuria at younger ages highlights importance of metabolic assessment in early childhood. Bilateral renal involvement, high number/size of cystine stones and their recurrent nature may make cystinuria patients more vulnerable to renal parenchymal damage and more resistant to treatments.